2023
DOI: 10.1002/anie.202306497
|View full text |Cite
|
Sign up to set email alerts
|

A Photosensitizing Metal–Organic Framework as a Tandem Reaction Catalyst for Primary Alcohols from Terminal Alkenes and Alkynes

Abstract: Owing to the wide and growing demand for primary alcohols, the development of efficient catalysts with high regioselectivity remains a worthwhile pursuit. However, according to Markovnikov's rule, it is a challenge to obtain primary alcohols with high yields and regioselectivity from terminal alkenes or alkynes. Herein, we report the synthesis of a photosensitizing two‐dimensional (2D) metal–organic framework (MOF) from cyclic trinuclear copper(I) units (Cu‐CTUs) and a boron dipyrro‐methene (Bodipy) ligand. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…18,19 Recently, by combining the chemistry of MOFs and covalent organic frameworks (COFs), 20 we and other groups have successfully synthesized various functional CTU-based MOFs linked by dynamic covalent bonds, which allows us to bring the merits from MOFs and COFs. 21–29 Due to the built-in characteristics, CTU-based MOFs exhibit not only highly ordered structures and controllable porosities, but also unique catalytic activity for various organic transfer reactions. 26–29 It has been found that Cu( i ) CTUs exhibited an electron-deficient surface, 30 which can be used as electron acceptor building blocks to construct D–A MOFs via dynamic covalent chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Recently, by combining the chemistry of MOFs and covalent organic frameworks (COFs), 20 we and other groups have successfully synthesized various functional CTU-based MOFs linked by dynamic covalent bonds, which allows us to bring the merits from MOFs and COFs. 21–29 Due to the built-in characteristics, CTU-based MOFs exhibit not only highly ordered structures and controllable porosities, but also unique catalytic activity for various organic transfer reactions. 26–29 It has been found that Cu( i ) CTUs exhibited an electron-deficient surface, 30 which can be used as electron acceptor building blocks to construct D–A MOFs via dynamic covalent chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Photosensitization is a crucial step for realizing light-to-chemical energy conversion in photosynthesis, and the development of efficient light-harvesting systems (LHSs) is highly desirable. In principle, promising LHSs should feature combinational merits, including broadband light absorption for solar energy utilization, order architectures for electron and energy transfer, and multiple functional moieties for synergism. To meet these requirements, various crystalline LHSs have been exploited, such as metal–organic framework (MOFs), covalent organic framework (COFs), and supramolecular systems. Unfortunately, in most of the LHSs, only the monochromophore was used as a photosensitizer (PS), showing limited solar spectral absorption for practical photocatalytic application.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Inspired by the functional complexity of biomolecular systems, different metal ions have been introduced into the metallo-cages with aim to prepare highly advanced structures as well as fulfil specific applications. 19–22…”
Section: Introductionmentioning
confidence: 99%